Analisis Prediksi Debit Sungai Amprong Dengan Model Arima (Autoregressive Integrated Moving Average) Sebagai Dasar Penyusunan Pola Tata Tanam - Wiwin Sri Rahayu; Pitojo Tri Juwono; Widandi Soetopo (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2019)
An accurate determination of water availability in the 10-day period of the Amprong River has an important role in the planting system to support the agricultural production process in DI. Kedungkandang, because if the availability of water is not precisely determined, there will be an error in regulating irrigation water and its use is not as expected. To overcome these problems, an analysis system is needed that is able to make predictions well. One of the time series models is the ARIMA (Autoregressive Intregated Moving Average) model. The model was built by 9 period discharge data, namely 2008/2009 until 2016/2017, to predict the discharge of period 2017/2018. Of the ten tentative models obtained, there are only five models that are worth using. The best model is the ARIMA model (2,0,1) (1,2,1) 36 with the value of MSE = 22,90; KR = 6.00; MSD = 8.05; MAD = 2.04; MAPE = 18.53 and MPE = -8.98. In second crop season the crop intensity of paddy increased from 55.79% to 64.50%, and the production of GBK increased by 13.50%. While the third crop season paddy crop intensity increased from 37.22% to 49.99%, and GBK production increased by 25.54%.